Clinical potential of sensory neurites in the heart and their role in decision-making - Tendulkar, Mugdha; Tendulkar, Reshma; Dhanda, Parmdeep Singh; Yadav, Alpa; Jain, Mukul; Kaushik, Prashant (Frontiers in Neuroscience, 2024)
The process of decision making is quite a complex process involving different aspects of logic, emotion and intuition. The process of decision making can be summarised as choosing the best alternative among a given plethora of options in order to achieve the desired outcome. This requires establishing numerous neural networks between various factors associated with the decision and creation of possible combinations and speculating their possible outcomes. In a nutshell, it is a highly coordinated process consuming majority of the brain's energy. It has been found that the heart comprises an intrinsic neural system which contributes not only to the decision making process but also in the short and long term memory. There are about 40,000 cells present in the heart known as sensory neurites which play a vital role in memory transfer.Heart is quite a mysterious organ which functions as a blood-pumping machine, endocrine gland and also possesses a nervous system. There are multiple factors which affect this heart ecosystem and it directly affects our capability of decision-making. These interlinked relationships hint towards the sensory neurites which modulate cognition and mood regulation. This review article aims at providing deeper insights into the various roles played by sensory neurites in decision-making and other cognitive functions. The article highlights the pivotal role of sensory neurites in the numerous brain functions & it also meticulously discusses the mechanisms through which they modulate their effects.